2017
DOI: 10.1007/s00038-017-0983-4
|View full text |Cite
|
Sign up to set email alerts
|

Food swamps by area socioeconomic deprivation in New Zealand: a national study

Abstract: Objectives A nationwide spatial analysis of community retail food environments in relation to area socioeconomic deprivation was conducted in New Zealand.Methods Addresses from about 20,000 registered food outlets were retrieved from all 66 Councils. Outlets were classified, geocoded and (spatially) validated. The analysis included 4087 convenience, 4316 fast food/takeaway and 1271 supermarket and fruit/vegetable outlets and excluded outlets not considered 'healthy' or 'unhealthy'. The population-weighted dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
3
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 33 publications
6
47
3
3
Order By: Relevance
“…Our study may lack power to detect such distal effects or unobserved effects or a suppressor variable could be operating. 23 However, previous studies detecting associations may result from residual confounding through social disadvantage; these associations are consistent throughout the literature between location of fast-food outlets and deprivation 6 and between deprivation and BMI. 24 25 This suggests that focusing on the role of social disadvantage rather than the fast-food outlets may yield more effective policy gains.…”
Section: Discussionsupporting
confidence: 80%
“…Our study may lack power to detect such distal effects or unobserved effects or a suppressor variable could be operating. 23 However, previous studies detecting associations may result from residual confounding through social disadvantage; these associations are consistent throughout the literature between location of fast-food outlets and deprivation 6 and between deprivation and BMI. 24 25 This suggests that focusing on the role of social disadvantage rather than the fast-food outlets may yield more effective policy gains.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, research by Pearce, Day, et al () analysed the role of neighbourhood access to retail provision of healthy and affordable food, again finding that access to a range of retail options was better in highly deprived areas. More recently, research by Sushil et al () has also confirmed such relationships, demonstrating that food swamps in New Zealand are stratified by deprivation. GIS is an effective tool for exploring the aetiology of health outcomes, particularly in regard to interactions with the built environment and deprivation.…”
Section: Introductionmentioning
confidence: 83%
“…Research on the food environment conducted within North America demonstrates clear spatial patterns between areas where there is little or no access to healthy foods—“food deserts,” socio‐economic status and health (Moore & Diez Roux, ; Morland, Wing, Diez Roux, & Poole, ; Smoyer‐Tomic et al, ; Walker, Keane, & Burke, ). Internationally relationships have not been as clear with research showing mixed results and in many cases demonstrating larger concentrations of outlets, both healthy and unhealthy, in highly deprived areas—“food swamps” (Duran, Diez Roux, Latorre, & Jaime, ; Feng et al, ; Macdonald, Ellaway, & Macintyre, ; Macintyre et al, ; Macintyre, McKay, Cummins, & Burns, ; Maguire, Burgoine, & Monsivais, ; Maguire, Burgoine, Penney, Forouhi, & Monsivais, ; Pearce, Blakely, Witten, & Bartie, ; Pearce, Day, & Witten, ; Pearce, Witten, Hiscock, & Blakely, ; Sushil, Vandevijvere, Exeter, & Swinburn, ; Svastisalee et al, ). Current research findings, while mixed, indicate that contextual associations between the food environment and socio‐economic deprivation may help to explain unequal spatial variations in negative health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, a government tax on unhealthy food and drink such as a sugar tax, or the removal of the goods and services tax on healthy food and drink (such as fruits, vegetables and plain milk) may have important public health implications both on what children purchase as well as the apparent preference for unhealthy food outlets to be located near schools and in areas of high deprivation (Vandevijvere and Swinburn 2015). Doing so may also be an important step towards reducing the inequitable distribution of poor health outcomes that can occur as a result of a diet high in unhealthy food and drink (Sushil et al 2017).…”
Section: Discussionmentioning
confidence: 99%